Development and Psychometric Evaluation of Family Caregivers’ Hardiness Scale: A Sequential-Exploratory Mixed-Method Study - Hosseini, Lida; Sharif Nia, Hamid; Ashghali Farahani, Mansoureh (Frontiers in Psychology, 2022)
Objective: Caring for patients with Alzheimer's disease is a stressful situation and an overwhelming task for family caregivers. Therefore, these caregivers need to have their hardiness empowered to provide proper and appropriate care to these older adults. From the introduction of the concept of hardiness, few studies have been conducted to assess the hardiness of caregivers of Patients with Alzheimer. Presumably, one reason for this knowledge gap is the lack of a proper scale to evaluate hardiness in this group. This study was conducted to develop a reliable and valid Family Caregivers’ Hardiness Scale (FCHS) to measure this concept accurately among Iranian family caregivers sample. Methods: This study is a cross-sectional study with a sequential-exploratory mixed-method approach. The concept of family caregivers’ hardiness was clarified using deductive content analysis, and item pools were generated. In the psychometrics step, the samples were 435 family caregivers with a mean age of 50.26 (SD ±13.24) and data was gathered via an online form questionnaire. In this step, the items of the FCHS were evaluated using face and content validity. Then, the factor structure was determined and confirmed using exploratory factor analysis and confirmatory factor analysis followed by convergent and divergent validity respectively. Finally, scale reliability including stability and internal consistency were evaluated. Results: The finding revealed that FCHS consists of five-factor including Religious Coping” (5 items), “Self-Management” (6 items), “Empathic Communication” (3 items), “Family Affective Commitment” (3 items), and “Purposeful Interaction” (4 items) that explained 58.72% of the total variance. The results of confirmatory factor analysis showed a good model fit. Reliability showed acceptable internal consistency and stability. Conclusion: Based on results of psychometric evaluation of the FCHS, turned out that the concept of hardiness in Iranian family caregivers is a multidimensional concept that is most focused on individual-cultural values, emotional family relationships and social relationship. The designed scale also has acceptable validity and reliability features that can be used in future studies to measure this concept in family caregivers.